A national advanced training program for laparoscopic radical gastrectomy has a positive impact on surgical trainees: A before and after study (ATP-LRG-1). (August 2022) - Wang, Zu-Kai; Lin, Jian-Xian; Huang, Jiao-Bao; Lu, Jun; Huang, Ze-Ning; Xie, Jian-Wei; Wang, Jia-Bin; Chen, Qi-Yue; Cao, Long-Long; Lin, Mi; Tu, Ru-Hong; Lin, Ju-Li; et al.
Abstract: Background: Due to the high technical requirements of laparoscopic radical gastrectomy (LRG), establishing an effective training system to promote clinical technology and operation specifications is necessary. We aimed to evaluate the effect of a national advanced training program for LRG (ATP-LRG). Materials and methods: The contents of the training include the following: 1) detailed technique descriptions; 2) prevention and solving of intraoperative complications; 3) live surgery performance; 4) theory and practice of clinical research; 5) comments on trainees' videos; and 6) questions, answers, and discussions. This retrospective before and after study surveyed 875 trainees from January 2015 to October 2020. Endpoints were general surgical skills (GSS), laparoscopic gastrectomy acceptance (LGA), and clinical research possibilities (CRP). The analysis took place in December 2021. Results: The response rate was 70.5% (617/875). ATP-LRG reportedly had a positive impact on the LRG practice of 99.5% (614/617) of trainees. Their GSS (before vs. after: 16.5 ± 3.7 vs. 20.3 ± 3.1, P < 0.001), LGA (4.2 ± 0.9 vs. 4.6 ± 0.7, P < 0.001), and CRP (2.6 ± 1.2 vs. 3.2 ± 1.1, P < 0.001) significantly improved. The improvement in GSS for those with professional titles of associate chief surgeons and below was significantly higher than that for chief surgeons (4.0 ± 3.0 vs 3.3 ± 2.4, P = 0.017), while those of LGA and CRP were not. The annual number of operations before training was negatively correlated with improvement in GSS (P < 0.001, Pearson's correlation coefficient: 0.14). Multivariate logistic regression showed that those with professional titles of associate chief surgeons and below (odds ratio [OR]: 1.719, 95% confidence interval [CI]: 1.038–2.846, P = 0.035), and with annual number of operations before training being <60, (OR: 5.257, 95% CI: 2.573–10.742, P < 0.001) were most prone to high-GSS improvement. Conclusion: The nationwide ATP-LRG facilitates the improvement of trainees' GSS, LGA, and CRP levels. Surgeons with lower professional titles and fewer performed operations are most likely to improve their GSS through training. Highlights: The advanced training program for laparoscopic radical gastrectomy (ATP-LRG) is feasible. The ATP-LRG has a positive impact on almost all trainees. Surgeons with lower professional titles are more likely to improve their general surgical skills (GSS). Surgeons with fewer performed operations are also prone to high-GSS improvement through training.